A multifunctional and highly stretchable electronic device based on silver nanowire/wrap yarn composite for a wearable strain sensor and heater. Issue 43 (17th October 2019) - Zhao, Min; Li, Dawei; Huang, Jieyu; Wang, Di; Mensah, Alfred; Wei, Qufu
Abstract : Stretchable and wearable electronics, as a well-researched engineering frontier, can be applied in human motion detection, thermal therapy, personal healthcare monitoring and smart human–machine interactions. Abstract : Stretchable and wearable electronics, as a well-researched engineering frontier, can be applied in human motion detection, thermal therapy, personal healthcare monitoring and smart human–machine interactions. In this study, a multifunctional textile-based electronic device with combined strain sensing and heating capabilities was successfully fabricated from silver nanowire/wrap yarn via a facile and scalable fabrication approach. The wearable electronic device possesses favorable sensitivity, high conductivity (resistance ≈ 36 Ω cm −1 ) as well as large strain range (tolerable strain up to 200%). When the functionalized yarn served as a strain sensor, it exhibited fast, reproducible and stable responses under various tensile loadings. In addition, the strain sensor showed favorable electromechanical reliability and durability (1000 cycles). Furthermore, the strain sensor could detect large-scale human movements when directly attached to elbow, wrist or knee. When the composite served as a heater, it presented high heating temperature, homogeneous temperature distribution, fast thermal response, low operation voltage (2–6 V) and stability in repeated and long-term use. Based on the superior performance, the wearable electronic device holds tremendous promise for human motion monitoring, health tracking and thermotherapy.